Growth volatility in the inflation-targeting regime: Evidence from Indonesia - Haryo Kuncoro; Fafurida Fafurida; Izaan Azyan Abdul Jamil (AIMS Press, 2024)
Low and stable inflation and exchange rates are the main objectives of inflation-targeting monetary policy. The internal and external stabilities are prerequisites for promoting economic growth. Using a two-stage GARCH, we investigated the effect of inflation instability and exchange rate unpredictability on the economic growth uncertainty in the case of Indonesia over the period 2000(1)– 2022(12). It was evident that both inflation instability and exchange rate unpredictability hurt output growth. The impact of inflation instability was higher than that of exchange rate unpredictability. While the output growth was higher in the post inflation-targeting regime adoption, the effect of real exchange rate instability was greater than that of nominal exchange rate unpredictability. Those findings suggested that the monetary authority should strengthen their commitment to achieve the inflation target range. The sharper focus on the inflation stability might avoid the monetary authority conducting twofold targets of inflation and exchange rate stability to stimulate economic growth.